Modeling Factors Influencing Purchase Intention of Eco-Friendly Packaging in Malaysia - Hoo, Wong Chee; Lin, Ang Sin; Wolor, Christian Wiradendi; Shaznie, Aminath; Prompanyo, Manoch (Journal of Ecohumanism, 2024)
Consumer choices for environmentally friendly items have been affected by the increased global awareness of environmental sustainability. Theory of Planned Behavior (TPB) will be used for this research. Using a thorough consumer survey, this study looks at Malaysians' desire to buy environmentally friendly packaged goods, as well as the variables that affect their choices. This study aims to determine the causal relationship between the dependent variable (purchase intention) and the independent variables (attitude, subjective norm, and perceived behavioral control). The questionnaire distributed online to a total of 384 Generation Z individuals in Malaysia through Google Forms. SmartPLS 4 software used to analyze the data in this study which included measurement model and structural mode. It used to determine the relationship between dependent and independent variables. The results show that perceived of behavioral control, attitude, and subjective norm all affect purchase intention. However, this study has some limitations and it will described in in the following section. And some suggestions for further research recommended in the following section as well.